Learning trajectory dan obstacle mahasiswa dalam mengabstraksi berdasarkan konstruk Teori Valsiner - Sri Trito Madawistama (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2017)
The learning process was generally conventional in nature regardless of the obstacle experienced by students, it is important to figure out the trajectory do obstacle students, so expect students as prospective teachers can develop its mathematical abstraction ability. This paper discusses about the Trajectory (Path), the Obstacle (any difficulty) in abstraction, designed based on the learning theory of constructivist approach valsiner. The purpose of this research is to examine the obstacle of students through the search trajectory. The method of this study refers to the development model of Tjeerd Plomp with qualitative approaches. The subject is students who follow courses semester V opportunity Theory in University Mathematics Education courses Siliwangi. Search results: learning trajectory through the obstacle findings obtained a student’s difficulty in understanding the concept of the material making it harder in resolving the question of the story related to everyday life–day. The second obstacle, namely the inability of students in represents the answer to question into a word–the word, sentence or notation. The third obstacle, the student still difficulty in connect between one concept with another concept. The fourth obstacle is experiencing confusion due to not knowing the techniques and characteristics of the finish reserved. There are three fundamental questions in this paper, namely what, why and how to develop the trajectory and know the obstacle of students in the process of abstraction based on the theory of Valsiner?Keywords: Trajectory, Obstacle, Abstraction, Valsiner Theory.